The influence of maceration time and enological media in polyphenolic contents of the Vranac wines - Raičević Danijela; Božinović Zvonimir; Petkov Mihail; Mijović Slavko; Popović Tatjana (Agroznanje, 2011)
This work, based on three-year research, analyses the influence of maceration time, with applying of different enological media, in the content of total polyphenols, anthocyanins, colour intensity and hue of the Vranac wines. The enological media, used during the research, are: selected yeast, enzyme, oak chips and tannin. Grapes processing was done in a buttery placed on the property is in Ljeskopolje area, Podgorica subregion. The transition dynamics of the Vranac grape polyphenolic substance into its wine during maceration was being observed every day within fourteen days. The results from this work show that the time of maceration affects polyphenolic content of wine contingent upon applying of different enological media. Total polyphenolic content is increasing from the beginning of maceration and reaching the maximum on the fourteenth day with all the variants. The total content of anthocyanins and colour intensity are increasing in the early phase of fermentation coming up to the maximum between the fifth and seventh day. Afterwards their content is decreasing. Colour hue is inversely proportional to the colour intensity of wine. Enological substances are increasing the content of polyphenols, compared to the control wine, whereas the enzyme had the greatest impact.